Influence of Arabic language and Literature in the languages and literatures of Islamic peoples in South Asia and Malay Archipelago in Southeast Asia - Shamsuddin (Dr.), Salahuddin Mohd.; (Dr.) Dean, Siti Sara Binti Hj. Ahmad (IJRDO- Journal of Educational Research, 2017)
The national intolerance and arrogance often leads to the isolation of national language andliterature from the useful intellectual and cultural currents help to enrich the language andliterature. The Languages and Literatures by the connection among the different languages andliteratures gain the cultural reflections and social concepts vary in different societies andenvironments.We present a manifestation of the links among the languages and literatures of Islamicpeoples, and the influence of Arabic in the languages of Islamic Literatures, such as Persian, Urdu,Turkish and Malay and other languages and their literatures. All of these languages and literaturesare influenced in their depths and dimensions by the Islamic civilization, and in any way we cannotcut the link amongst them, because they all present the images of Islamic nation and civilization.The languages of these literatures are affected by Arabic language, as there are countless Arabicwords in their use, this is an evidence that they all branched out from one origin, which is thereligion of Islam, therefore, who will study them study the civilization of Islam in all of itsmanifestations. The impact resulted from the mixing and contact between two nations is verynecessary and a normal thing, which is very important, because it leads the national languages andliteratures to alleviate the intolerance. It should be also noted that the best part of these literaturesis that one, which was produced after the intellectual convergence between these literatureswithout the feeling of national intolerance.